Frequency-Domain Receivers for Rate-1 Space-Time Block Codes - Silva, Mário Marques da (2009)
This paper considers iterative frequency-domain receivers for block transmission techniques with rate-1 Space Time Block Coding (STBC) for two and four transmit antennas using both Orthogonal Frequency Division Multiplexing (OFDM) and Single-Carrier (SC) schemes. The proposed receiver includes an interference canceller which enhances the performance of the non-orthogonal STBC scheme with 4 transmit antennas, allowing performances close to those of orthogonal codes. Our performance results show that combining STBC with block transmission techniques allows excellent performances.